Myasthenia Gravis mimics: An audit of cases identified at Groote Schuur Hospital over 20 years - Neshuku, Saara Ndinelago (Department of Medicine, 2020)
Background: Myasthenia gravis (MG) is characterised by fatigable muscle weakness. The diagnosis is made clinically and supported by ancillary tests such as electrophysiological studies, autoantibodies and pharmacological responses. Autoimmune MG will respond to immune therapy. Although there are several case reports of patients who were incorrectly diagnosed as MG, this study describes the MG mimics encountered at Groote Schuur Hospital, Cape Town, over a period of 20 years. Aims & Methods: To describe the MG mimics captured in the MG database (1996 to 2017) by final diagnosis, the age at symptom onset, the time delay and clues which led to the final diagnosis. Results: There were 31 cases identified; 10 were probable congenital myasthenic syndromes (CMS), 6 functional neurological symptoms (FNS), 6 motor neuron disease (MND) variants, 3 mitochondrial cytopathies, 4 had definite or probable muscular dystrophy (MD), 1 progressive supranuclear palsy and 1 with a multiple sclerosis brainstem relapse. Median age at symptom onset was 10 years for CMS, 18 for mitochondrial cytopathies, 53 for FNS, 58 for the muscular dystrophy cases and 63 years for those with MND. The median time delay between the false “MG” diagnoses to the reviewed diagnosis, which also corresponds to the time on immunotherapies, was 45 months in CMS, 48 months in mitochondrial cytopathy, 4 in MND, and less than 3 months in FNS, MD, PSP and MS. The most important factor for reviewing the diagnosis was treatment unresponsiveness to immune therapy. Some of the CMS and mitochondrial cytopathy cases were treated with immune therapies for many years, without responsiveness, before referral to our centre. Additional features for CMS were childhood onset, family history of similar symptoms and, although no response to immune therapies, they responded to pyridostigmine +/- salbutamol. Mitochondrial cytopathies had long duration of symptoms and the diagnosis was confirmed by mitochondrial DNA deletion detection. MND patients showed disease progression within a few weeks despite some transient improvement with anticholinesterases. The FNS diagnoses were based on signs which were inconsistent and symptoms resolved after psychotherapy. Two MD cases (myotonic muscular dystrophy and probable oculopharyngeal muscular dystrophy, respectively) presented with respiratory failure, and could not be weaned off invasive ventilation. Conclusion: The main points are that, not all patients with ptosis and fatigable symptoms have myasthenia gravis. Non-responsiveness to immune therapies should raise suspicion of an alternative diagnosis and prompt referral to a specialist clinic. Transient modest improvement in bulbar and limb muscle symptoms have been observed in patients with early manifestations of motor neuron disease.